Dividend Policy As Moderating The Effect Of Intellectual Capital And Insider Ownership On Stock Return - Akhmad Sigit Adiwibowo; Nurma Yunitasari; Putri Nurmala (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2022)
This study aims to determine the effect of Intellectual Capital and Insider Ownership on Stock Return, and determine the effect of Dividend Policy in moderating the relationship beetween Intellectual Capital and Insider Ownership on Stock Return in LQ45 companies listed on Indonesia Stock Exchange for the 2016-2020 period. Based on the purposive sampling method, a sample of 26 companies was obtained. The analytical method used is descriptive statistical method using a moderation regression analysis tool. The results of this study indicate that Intellectual Capital and Insider Ownership have a significant effect on Stock Return. Dividend Policy can moderate the effect of Intellectual Capital on Stock Return. Dividend Policy is not able to moderate the effect of Insider Ownership on Stock Return.